Institutional forms of organization of management of the agricultural sector development - Ковальова, О. В. (Scientific Progress & Innovations, 2012)
In this article the author on the neoinstitutional methodological basis has grounded the matrix of institutional forms of agricultural sector development by vectors «centralization – decentralization» of making administrative decisions, «the economic and national interests». The matrix describes the institutional forms of markets, hierarchy, heterarchy and other forms of agricultural sector development as the organizational form of national socio-economic and commercial economic interests compromise in a polycentric decision making system as prerequisites for the formation of the institutional environment of joint action of public and private partners. The types of hybrid forms of governance at the sectoral level are defined.